2019
DOI: 10.2478/ncr-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Shrinkage Cracking of Self-compacting Concrete: Influence of Capillary Pressure and Dormant Period

Abstract: This research investigates the effect of capillary pressure and the length of the hydration dormant period on the plastic shrinkage cracking tendency of SCC by studying specimens produced with different w/c ratios, cement types and SP dosages. A relationship between the capillary pressure rate and the length of the hydration dormant period is defined, which can explain the cracking severity of the concrete when the volumetric deformation is unknown. The results show, that the cracking tendency of SCC was the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
2
3
0
1
Order By: Relevance
“…This value is somewhat lower to −5.2 and −6.5 mm/m in SC-M-1-20RHA and SC-M-1-10CC+10RHA, respectively. This high plastic shrinkage value of SC-M at this stage is due to the particles settlement caused by gravity leading to an increased packing density of the SC-M and forcing the free water to rise to the surface of the SC-M, resulting in bleeding, as previously explained by [ 69 ], and evaporation of moisture from the surfaces of the SC-M leading to the formation of water menisci, which eventually create a negative capillary pressure that contracts the SC-M particles and consequently causes volumetric contraction, similar to was reported by [ 70 , 71 ]. It has been reported that the use of shrinkage-reducing admixtures (SRA) reduced the plastic shrinkage of SCC at this stage of hydration by reducing the internal friction angle between SCC particles due to their high fluidity and delaying the setting time of SCC [ 69 ].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This value is somewhat lower to −5.2 and −6.5 mm/m in SC-M-1-20RHA and SC-M-1-10CC+10RHA, respectively. This high plastic shrinkage value of SC-M at this stage is due to the particles settlement caused by gravity leading to an increased packing density of the SC-M and forcing the free water to rise to the surface of the SC-M, resulting in bleeding, as previously explained by [ 69 ], and evaporation of moisture from the surfaces of the SC-M leading to the formation of water menisci, which eventually create a negative capillary pressure that contracts the SC-M particles and consequently causes volumetric contraction, similar to was reported by [ 70 , 71 ]. It has been reported that the use of shrinkage-reducing admixtures (SRA) reduced the plastic shrinkage of SCC at this stage of hydration by reducing the internal friction angle between SCC particles due to their high fluidity and delaying the setting time of SCC [ 69 ].…”
Section: Resultssupporting
confidence: 72%
“…Finally, after 16 h of hydration, the plastic shrinkage remains constant until the end of the measurement. The reason for the plastic shrinkage of the SC-M beyond 7 h of hydration could be due to the continuous evaporation of moisture from the SC-M surfaces and volume reduction due to water consumption by the hydration process, as previously observed by [54,70,71]. In general, the reduction in plastic shrinkage after 7 h of hydration due to the partial replacement of CC and RHA in SC-M could be attributed to the fact that both act as nuclei for the formation of hydration products at an early time of hydration, thereby increasing the volume of hydration product and densifying the SC-M microstructure, as observed previously by [73] when studying the dominant factors on the early hydration of metakaolin-cement paste.…”
Section: Formation Of Hydrate Phases From the Hardened Scpsupporting
confidence: 56%
“…Increasing the evaporation rate increases the build-up rate of the negative capillary pressure in concrete and vice versa when the evaporation rate is decreased [4]. Numerous researchers have also shown that the negative capillary pressure build-up is affected by factors such as particle size distribution, bleeding, admixtures, additions, specimen geometry and the water/cement ratio [3,6,12,[14][15][16][17]. Due to all these factors influencing the negative capillary pressure build-up, the capillary pressure mechanism has been identified in the literature as the primary mechanism for plastic shrinkage [4,10,14,18].…”
Section: Figmentioning
confidence: 99%
“…When plastic shrinkage occurs and the concrete is restrained, tensile stresses are induced and if the concrete did not develop sufficient strength to withstand the induced stresses, plastic shrinkage cracks will form [1,2]. The induced tensile stresses are caused by the build-up of negative capillary pressure within the fresh concrete [3]. If the negative capillary pressure builds up at a high rate and reaches a critical capillary pressure, plastic shrinkage cracking may occur [4].…”
Section: Introductionmentioning
confidence: 99%
“…e shrinkage of a GRC-PLC composite panel includes temperature shrinkage, drying shrinkage, plastic shrinkage, carbonization shrinkage, and autogenous shrinkage. Faez Sayahi et al [39] believe that cement shrinkage and deformation is the main cause of cracking. erefore, the composite panel cracks can be reflected by monitoring the shrinkage strain of the panel.…”
Section: Drying Shrinkage Performance Of Grc-plc Compositementioning
confidence: 99%